Co-administration of rifampicin and Boswellia serrata mitigates testicular toxicity caused by Aflatoxin B1 - Korkak, Fatih Ahmet; Alkac, Zeliha Keskin; Arkali, Gozde; Gungor, Ibrahim Halil; Yuksel, Burak Fatih; Incili, Canan Akdeniz; Dagoglu, Gurdal (Pergamon-Elsevier Science Ltd, 2025)
The current study was aimed to investigate the effect of rifampicin (Rif), a stimulator of P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP), on limiting the passage of AFB1 (Aflatoxin B1) into testicular tissue. The second objective was to examine the potential protective effects of Boswellia serrata extract (BSE), which exhibits a strong antioxidant capacity, alone or incombination with Rif against testicular damage induced by AFB1. A total of 49 male Sprague-Dawley rats were randomly divided into seven experimental groups as follows: control (placebo), Rif (10 mg/kg), BSE (500 mg/kg), AFB1 (0.75 mg/kg), AFB1+Rif, AFB1+BSE, and AFB1+Rif + BSE. The rats were administered AFB1, Rif, and BSE for seven days. The result of this study indicated that Rif decreased the amount of AFB1 permeating the testicular tissue by stimulating the expression of P-gp and BCRP. The administration of the combination of BSE and Rif resulted in a reduction of oxidative stress, apoptosis, improvement in sperm function parameters, and an increase in serum testosterone levels. These effects contributed to the improvement of impaired testicular structure. The result of this study revealed that the Rif can potentially serve as an efficacious therapeutic agent and the administration of BSE exhibited a reduction in testicular damage induced by AFB1. However, the combination of BSE and Rif provided more effective protection than using alone.
Keywords: Aflatoxin B1; Rifampicin; Boswellia serrata; P-glycoprotein; BCRP; Testis